2002
DOI: 10.1007/s00264-002-0402-0
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps torque curve pattern in patients with anterior cruciate ligament injury

Abstract: We measured torque curve pattern and quadriceps muscle strength with the knee slightly flexed in 48 patients with an anterior cruciate ligament injury, and analyzed the factors associated with reduced quadriceps strength. Strength was measured under isokinetic contraction, and concentric and eccentric contractions were studied. Strength was significantly lower in the injured knee, which also showed abnormal patterns of torque curve. In addition to the rapid downward slope pattern usually associated with concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
26
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 9 publications
7
26
0
4
Order By: Relevance
“…Solomonow et al (1987) attributed the irregular pattern of the isokinetic curve in ACL deficient patients to the temporary subluxating tibia. This observation has been confirmed by others as well, although not in a numerical manner (Dvir et al, 1991;Ikeda, 2002;Ayalon et al, 2002). Apart from the aforementioned mechanical disturbance, there seems to be a direct link between ACL and muscles around the knee (Dyhre-Poulsen and Krogsgaard, 2000).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Solomonow et al (1987) attributed the irregular pattern of the isokinetic curve in ACL deficient patients to the temporary subluxating tibia. This observation has been confirmed by others as well, although not in a numerical manner (Dvir et al, 1991;Ikeda, 2002;Ayalon et al, 2002). Apart from the aforementioned mechanical disturbance, there seems to be a direct link between ACL and muscles around the knee (Dyhre-Poulsen and Krogsgaard, 2000).…”
Section: Introductionsupporting
confidence: 81%
“…Anterior cruciate ligament (ACL) injury has various negative implications for thigh muscle function, including reduction of muscle strength (Lorentzon et al, 1989;Wojtys and Huston, 2000a, b) and instability of torque generation (Dvir, 1995;Ikeda, 2002). Extension and flexion strength after ACL rupture is assessed by isokinetic dynamometry, which involves measurements mainly of the classical parameters such as peak torque, total work and average power (Benjuya et al, 2000;St.…”
Section: Introductionmentioning
confidence: 99%
“…Westing et al 14 demonstrated that the method error and standard deviation for this measure is approximately 8% and 13 NÁm, respectively. With 80% power and an alpha level error of 5%, at least 10 subjects were needed to detect greater than the clinically significant difference in knee extensor strength (approximately 11%; Kannus et al 15 ; McNair 16 ; Keays et al 17 ; Ikeda et al 18 ) between test limbs. This study was approved by the Human Ethics Research Review Panel, Central Queensland University, Rockhampton, Australia.…”
Section: Neuromuscular Characteristics Following Aclrmentioning
confidence: 99%
“…Recovery after knee joint injury is complicated by persistent quadriceps weakness, decreased joint stability, and deficits in proprioception, all of these factors resulting in decreased neuromuscular control. 11,13,14 During the past decade, knee rehabilitation after ACL reconstruction has undergone a tremendous evolution, from a conservative approach of immobilization for 6 to 8 weeks followed by crutch training for 8 to 12 weeks, to functional rehabilitation that emphasizes immediate motion and weightbearing. 26 Proprioceptive training is also gaining recognition as an integral component of rehabilitation.…”
Section: Introductionmentioning
confidence: 99%